Assessment of the microbiological quality of pattern minas cheese commercialized in Uberlândia and Patos de Minas, Minas Gerais - Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Castro, Bruna Godoi [UNESP]; Raghiante, Fernanda [UNESP]; da Silva, Felipe Chaimsohn Gonçalves [UNESP]; de Azevedo, Everton Cruz [UNESP]; de Oliveira, Jéssica Fernandes [UNESP]; Velame, Marise Santiago [UNESP]; Garcia, Lorena Natalino Haber [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP]; Baldini, Eduardo Delbon [UNESP]; Possebon, Fábio Sossai [UNESP]; Biondi, Germano [UNESP]; et al. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Pattern minas cheese is a product developed with pasteurized milk, fermented with mesophilic cultures, and with the final addition of rennet. This cheese undergoes an artisanal maturation process and possesses a firm shell of yellowish color and striking and acidic flavor. Our study objective was to evaluate the microbiological quality of pattern minas cheese. We collected 40 samples from two micro regions (Uberlândia and Patos de Minas) of the Triângulo Mineiro and Alto Paranaíba mesor regions of the State of Minas Gerais, Brazil. The microbiological test results were recorded as counts of enterobacteria, Escherichia coli, coliforms at 35°C, coagulase-positive Staphylococcus and Salmonella spp. In the Patos de Minas micro region, the results were 45%, 35%, 20%, and 20% higher than 103 CFU/g for the counts of enterobacteria, Escherichia coli, coliforms at 35°C, and Staphylococcus coagulase-positive, respectively. Five percent of the analyzed samples were positive for Salmonella spp. in the Uberlândia micro region. Based on the findings of the microbiota in the cheese analyzed from the micro regions (Uberlândia and Patos de Minas), we concluded that the hygiene conditions in the manufacturing, handling, transport, and storage stages were precarious, requiring the implementation of Good Manufacturing Practices (GMP) systems, including Hazard Analysis and Critical Control Points (HACCP).
Avaliação microbiológica de queijo minas padrão comercializado em Uberlândia e Patos de Minas, Minas Gerais
Keywords: Hygiene; Microbiology; Pattern Minas Cheese; Quality